2001
DOI: 10.1074/jbc.c100401200
|View full text |Cite
|
Sign up to set email alerts
|

HIP1 Functions in Clathrin-mediated Endocytosis through Binding to Clathrin and Adaptor Protein 2

Abstract: Polyglutamine expansion in huntingtin is the underlying mutation leading to neurodegeneration in Huntington disease. This mutation influences the interaction of huntingtin with different proteins, including huntingtin-interacting protein 1 (HIP1), in which affinity to bind to mutant huntingtin is profoundly reduced. Here we demonstrate that HIP1 colocalizes with markers of clathrin-mediated endocytosis in neuronal cells and is highly enriched on clathrin-coated vesicles (CCVs) purified from brain homogenates. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
176
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 184 publications
(184 citation statements)
references
References 33 publications
7
176
1
Order By: Relevance
“…GST-ENTH MP90 (amino acids 1-137) (33) and GST-ENTH Af10 (amino acids 1-153) (3) were amplified by PCR using full-length cDNA templates and cloned between the EcoRI and BamHI sites of pGEX-2TK (Amersham Biosciences). GST-HIP1-ANTH (amino acids 1-125) and GST-HIP12-ANTH (amino acids 1-150) expression constructs were generated by PCR amplification from their respective full-length cDNAs (20,34), followed by cloning into the pGEX-6P vector (Amersham Biosciences). The 3Ј-end of each HIP construct was tagged with codons for three glycines followed by six histidine residues and a stop codon.…”
Section: Methodsmentioning
confidence: 99%
“…GST-ENTH MP90 (amino acids 1-137) (33) and GST-ENTH Af10 (amino acids 1-153) (3) were amplified by PCR using full-length cDNA templates and cloned between the EcoRI and BamHI sites of pGEX-2TK (Amersham Biosciences). GST-HIP1-ANTH (amino acids 1-125) and GST-HIP12-ANTH (amino acids 1-150) expression constructs were generated by PCR amplification from their respective full-length cDNAs (20,34), followed by cloning into the pGEX-6P vector (Amersham Biosciences). The 3Ј-end of each HIP construct was tagged with codons for three glycines followed by six histidine residues and a stop codon.…”
Section: Methodsmentioning
confidence: 99%
“…Two other proteins that contain ENTH domains, HIP1 and HIP1R, and their counterpart in S. cerevisiae, Sla2p, interact with the actin cytoskeleton as well as play a role in endocytosis (95,232,238,369,383,401). Phosphatidylinositides play a major role in regulating actin (404), and the ENTH domains of HIP1 and HIP1R may function to coordinate the assembly of endocytic coat proteins with changes in the actin cytoskeleton.…”
Section: Enth/anth Domainsmentioning
confidence: 99%
“…Hip1 is closely related to Hip1R (ϳ50% overall amino acid sequence identity) and has been implicated in the pathology of Huntington disease (Kalchman et al, 1997;Wanker et al, 1997). Similar to Hip1R, Hip1 has been shown to be enriched in CCVs, to colocalize with markers for receptor-mediated endocytosis, and to bind to other endocytic proteins (clathrin, AP-2; Metzler et al, 2001;Mishra et al, 2001;Waelter et al, 2001;Legendre-Guillemin et al, 2002). Recently, phenotypic analysis of Hip1 knockout mice suggested that Hip1 functions in receptor-mediated endocytosis (Metzler et al, 2003), similar to its yeast homologue, Sla2p.…”
Section: Introductionmentioning
confidence: 99%